Accurate analytical solution of the circular sector oscillation by the modified harmonic balance method. Issue 4 (December 2022) - Farea, Nadia M; Zayed, Mohra; Ismail, Gamal M
This paper aims to solve the nonlinear differential equation of the circular sector oscillator analytically via the modified harmonic balance method (MHBM). To assess the reliability and the precision of the present method, we have compared the obtained results with the global residue harmonic balance method, Akbari–Ganji's method, and numerical Runge–Kutta method which reveals that the MHBM is more reliable than others methods.